A Research Project to Improve Human Resource Record Management System of Nurses In A Teaching Hospital, Sri Lanka - Adikari, Pamila; Dalpatadu, Shanti (Jurnal Manajemen, 2020)
Background: Poor quality records management in Sri Lankan Hospital offices is a major dissatisfaction and demotivation for healthcare staff. An intervention research project to improve the record management of selected Human Resource (HR) records of nurses in an Office of a Tertiary Care Hospital in Sri Lanka was carried out to identify the gaps, implement improvements and to test the outcome. Grade promotion and annual increment HR processes considered for the improvements. Qualitative and quantitative techniques used for gap identification, planning of interventions and assessment of the effectiveness. A package of quality improvements initiatives implemented following literature review and stakeholder participation. Absence of instructions/sample filled-forms and issues in the document flow were the inconsistencies noted. The record processing time was 30.83 days with an SD of ±4.84 for completion of annual increments and 24.33 days with an SD of ±4.21 for authorisation of grade promotions. The package of interventions included e-based/ paper-based guides and specimen request forms and a document movement register to track the records. Increased accessibility, accuracy, improved quality, timeliness and improved traceability of submitted forms and improvements in the average time spent for annual increments and grade promotions noted; 17.52 days (SD ±3.39) and 12.13 days (SD ±2.33) respectively, a statistically significant reduction (p<0.05). Implementation of quality improvement interventions using computer-based initiatives with stakeholder participation can improve office management issues in the tertiary hospital setting.